Analysis of Subjective Fatigue Among Urban Transportation Drivers in Tataaran, North Sulawesi, Indonesia - Sudirham Sudirham; Tika Bela Sari; I Wayan Gede Suarjana (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
This study examines subjective fatigue among urban transportation drivers in Tataaran, Minahasa Regency, North Sulawesi where the occupation exposes individuals to stressors that can induce fatigue. The research aims to analyze the levels of subjective fatigue and identify contributing factors. A cross-sectional study was conducted from August to November 2024, involving 43 drivers. Data was collected using a structured questionnaire, including the Fatigue Severity Scale (FSS), to assess socio-demographic, work-related, and vehicle-related factors. The results indicate that increased age, daily work duration, irregular working hours, heavy driving workload, and uncomfortable vehicle ergonomics are significantly associated with higher subjective fatigue levels (p<0.05). Conversely, greater driving experience is significantly associated with lower subjective fatigue (p<0.05), while rest patterns and deposit targets showed no significant relationship with fatigue. In conclusion, urban transportation drivers in Tataaran experience significant subjective fatigue, influenced by a combination of occupational and individual factors.